Synthesis and evaluation of antifungal properties of a series of the novel 2-amino-5-oxo-4-phenyl-5,6,7,8-tetrahydroquinoline-3-carbonitrile and its analogues - Gholap, Atul R.; Toti, Kiran S.; Shirazi, Fazal; Kumari, Ratna; Bhat, Manoj Kumar; Deshpande, Mukund V.; Srinivasan, Kumar V. (Bioorganic & Medicinal Chemistry, 2007)
A series of 2-amino-5-oxo-4-phenyl-5,6,7,8-tetrahydroquinoline-3-carbonitrile and various analogues have been synthesized in excellent isolated yields starting from various arylidenemalononitrile and 3-amino-2-cyclohexen-1-one in 1-propanol as solvent at reflux temperature in the absence of any added catalyst. All the synthesized compounds were evaluated for their antifungal activity. The relationship between functional group variation and biological activity of the evaluated compounds is discussed in the article. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Antifungal activity; antiproliferative activity; arylidenemalononitriles; arylquinoline carbonitrile; Michael addition